O processo histórico de criação do livro “O direito na vida das crianças, vol. I” - Brito, Rafael Almeida Cró (My University, 2025)
The present research focuses on the creation process of the book "O Direito na Vida das Crianças, Vol. I" which presents rights and duties in a playful way. From birth, law is present in all social relationships that are established. The understanding of fundamental rights should begin within basic education in order to create future citizens who are knowledgeable about their rights and obligations. The primary objective of this work is to contribute to the education of citizens so they can understand their place in the world, recognize opportunities to transform it, and, in a protagonist trajectory, implement changes. The topics presented here should be integrated into the school's pedagogical proposal as a transversal theme and combined with the common efforts of an educational institution focused on the child as a citizen living in a democratic country, where the State itself confers this title. The text also highlights the deep interconnection between Law and History in the production of paradidactic material for basic elementary education. Thus, a mutual ethical commitment is assumed with a society that needs to be just and egalitarian. [resumo fornecido pelo autor]
A presente pesquisa tem como foco a apresentação do processo de criação do livro "O Direito na vida das Crianças, Vol. I", que indica os direitos e os deveres de uma forma lúdica. Desde que a pessoa nasce, o Direito é algo presente em todas as relações sociais que se estabelecem. A compreensão dos Direitos Fundamentais deve ocorrer a partir da educação básica para poder criar futuros cidadãos conhecedores de seus direitos e obrigações. O objetivo principal do trabalho consiste em colaborar com a educação de cidadãos, para que compreendam seu lugar no mundo, percebam oportunidades para transformá-lo e, num percurso de protagonistas, operem mudanças. Os tópicos aqui apresentados devem ser somados à proposta pedagógica da escola com um tema transversal e aos esforços comuns de uma instituição educacional centrada na criança cidadã, que vive num país democrático, no qual o próprio Estado confere esse título. O texto ressalta também a profunda interligação entre o Direito e a História na produção de um material paradidático para o ensino fundamental básico. Assume-se, assim, um compromisso ético mútuo com uma sociedade que precisa ser justa e igualitária. [resumo fornecido pelo autor]
Keywords: Direito das crianças; História - Estudo e ensino; Educação básica; Brasil. [Constituição (1988)]; Direitos fundamentais; Children's rights; History - Study and teaching; Basic education; Brazil. [Constitution (1988)]; Civil rights